Assessing Knowledge on Clubfoot Among Parents Having Children with Clubfoot Deformity - Alam, Zobaer; Haque, Md Monoarul; Bhuiyan, Md Rijwan; Islam, Md Shahinoor; Haque, Monirul; Islam, ASM Mazharul; Pradhania, Md Shafiullah (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: The burden of childhood disability as a public health problem in developing countries remains relatively unrecognized. One out of 750 children born in the world suffer from club foot among them 80% are in low and middle income countries. Most of these babies have limited access to receive effective treatment for their clubfoot due to lack o knowledge, awareness and some barriers. We actually dont know the level of knowledge of parents who have child with clubfoot deformity. The purpose of this study was to assess the level of knowledge of parents who have children with clubfoot during clubfoot treatment. Materials and Methods: This cross sectional study was conducted among 102 parents who have children with clubfoot deformity during its treatment in a selected clinic. The samples were selected purposively from the clinics where clubfoot treatment was given and face to face interview was done by using semi-structured questionnaire. Results: The mean (±SD) age of the respondents were 24.7 (±6.0) years where 87.3% (n=89) respondents ware female and 59.8 %(n=61) respondents educational status ware up to primary level. About 44.1% respondents started treatment of their child within 6 months of birth and 33% within 6 to 12 months where 57% (n=58) respondents are referred by health care professional to this clinics. About 93.1% of parents (n=95) said that they knew nothing about clubfoot deformity before their child was diagnosed where 97% are aware after diagnosis of their child. About 93.1% respondents knew the best time for treatment initiation where 59.8% respondents know the correct follow up time of clubfoot management. In case of knowledge of parents roles in the treatment of clubfoot about 91.2%, parents have knowledge weekly visit for treatment and 86.3% know the plaster care where 52.9% (n=54) parents have lack of knowledge about how to use the brace Conclusion: There is need to improve the communication skills of clinicians/health care providers offering treatment to children with clubfoot at the Clinics. Need to share information with the parents about the condition. Finally, there is need to emphasize of educating parents about plaster care and how to use brace. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22882 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 42-46